Reduction of Staphylococcus aureus bacteria collaboration in diabetic ulcers by giving virgin coconut oil - Nur, Siti Aisyah; Anggraini, Siska Sakti; Dafriani, Putri; Morika, Honesty Diana (International Journal Of Community Medicine And Public Health, 2020)
Background: Diabetic ulcers often result in amputations. The bacteria found in diabetic ulcers are Enterobacter sp, Staphylococcus aureus, Salmonella sp and Pseudomonas sp. Nursing management of ulcer patients has been attempted but nothing has been effective yet. Using virgin coconut oil (VCO) contains anti-inflammatory, antipyretic and has an analgesic effect to increase the formation of new blood vessels with faster wound healing. Aim was to study the effect of wound care by giving VCO on the colonization of Staphylococcus aureus bacteria in diabetic ulcers. Methods: Quasi-experimental research with the two-group pre-test and post-test design approach involved 36 diabetic ulcer patients with consecutive sampling by doing wound care for 4 days. The duration of treatment was 30-40 minutes. Data was taken by swab on wound fluid before and after the intervention. Bivariate analysis carried out t-independent test of DM ulcers. Results: The results showed the average number of colony staphylococcus in the intervention group before being given wound care with VCO 72.88, while after being treated with 38.88 wound VCO and the average results of the number of colony staphylococcus in the control group before being treated with NaCl 77.88, whereas after being treated with VCO 38.88 wound with NaCl 72.88 in the statistical test the p value is 0,000. Conclusions: There was a significant influence between the number of colony Staphylococcus in the control group and the intervention group.